Hamlet and the Late Renaissance Convention of Self-Addressed Speech: An Empirical Approach to Theatrical History. Issue 2 (November 2019) - Hirsh, James
Abstract : In late Renaissance English drama (from the late 1580s until the closing of the theaters in 1642) soliloquies were governed by a surprisingly precise and intricate convention. Plentiful, conspicuous, unambiguous, varied, and one-sided evidence demonstrates that soliloquies represented self-addressed speech as a matter of convention. Not surprisingly, Shakespeare was the most daring, imaginative, and profound exploiter of the convention, especially in Hamlet . One of the most interesting exploitations of the convention occurs in 3.3, which ends with three consecutive soliloquies, occupying a total of 63 lines, by two characters without any intervening dialogue between characters. In the course of the three soliloquies, a presumed contrast between Claudius's villainy and Hamlet's victimhood becomes a disturbing contrast between the villain's effort to repent and the victim's demonic purpose (to increase the population of hell) and eventually turns into a similarity between two characters who have both succumbed to evil. Shakespeare's most daring, imaginative, and profound exploitation of the convention occurs in 3.1. Plentiful, conspicuous, unambiguous, varied, and one-sided evidence demonstrates that Shakespeare designed the "To be, or not to be" episode to imply that the speech is not a genuine soliloquy but rather a feigned soliloquy. Arriving at the location to which he has been summoned by his deadly enemy ("We have closely sent for Hamlet hither"), Hamlet pretends to be oblivious to the conspicuous presence of Ophelia and pretends to talk to himself to mislead Ophelia, her meddlesome father, and ultimately the King into believing that he suffers from a debilitating melancholy in order to convince the King that he poses no threat.